Evaluation of Efficiency in Crime Control and Crime Prevention Programs - Carroll, John (American journal of criminal justice, 2010)
The purpose of the study is to evaluate and compare the efficiency of crime control and crime prevention programs. The focus on efficiency adds knowledge about quality of performance in criminal justice programs. The case study covers twelve-year implementation process of two juvenile justice programs in a local law enforcement agency. A Truancy Reduction Program (TRP) represents the crime control approach. A School Resource Officer Program (SROP) represents the crime prevention approach. The evaluation shows that the SROP produced far more efficient results than the TRP. The SROP demonstrates gradual improvement and efficient implementation. The TRP appears inefficient and, therefore, should have been revised in the midst of the implementation period. The study draws policy implications for designing more efficient crime control and crime prevention programs. The implications can be useful for law enforcement agencies that contemplate or implement such programs